Microfluidic‐based non‐enzymatic glycation enhances cross‐linking of human scleral tissue compared to conventional soaking. Issue 5 (27th January 2016) - Choi, Samjin; Moon, Sang Woong; Jin, Kyung‐Hyun; Shin, Jae‐Ho
Summary: We evaluated nano‐structural and chemical changes in human scleral collagen caused by non‐enzymatic glycation using AFM, Raman spectroscopy, and microfluidics. Twenty 8 × 2 mm 2 scleral strips (n = 5, each) were divided into four groups of pure sclera tissues (control group) and sclera tissues with incubation (1 hr in BSS and ribose) and preservation (23 hr in 90% ethanol) for 7 days (BSS + DR7 group) and 30 days (BSS + DR30 group) at room temperature, and 7 days in a microfluidic chip (BSS + DR + µF7 group). The BSS + DR7 and BSS + DR30 groups were incubated in a mixture of balanced salt solution (BSS) and 0.2 M D‐ribose in PBS, pH 7.4 containing 0.1% sodium azide, while the BSS + DR + µF7 group was incubated in the same solutions supplied by two inlet reservoirs from a microfluidic chip. The scleral tissues incubated in the microfluidic environment showed a clear irregular parallel arrangement of collagen fibrils with tangled fibrils. A Raman shift was observed at 919 cm −1 in the glycation groups. Non‐enzymatic glycation led to an increased in the density of scleral stromal collagen. Our method using non‐enzymatic glycation in a microfluidic environment successfully induced collagen cross‐linking. These in vitro results suggested that glycation can be used to strengthen connective tissues. SCANNING 38:421–426, 2016. © 2016 Wiley Periodicals, Inc.